Konstribusi Kompetensi Pedagogik dan Kepribadian Guru terhadap Hasil Belajar Siswa Pendidikan Vokasi - Khairul Insan; Aswardi Aswardi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
This research was conducted with the aim of knowing how much the contribution of pedagogic competence and teacher's personality competence to students' practical learning outcomes in the subject of electric power installation at SMK N 5 Padang. This type of research is quantitative research with correlation analysis methods. The subjects of this study were students of class XI TITL at SMK N 5 Padang in the 2022/2023 academic year. With a total of 38 students, the sample determination was carried out by means of Proportional Random Sampling. Data collection used a questionnaire and documentation, scoring the questionnaire instrument with a Likert scale and then the questionnaire was validated by a validator expert lecturer at the Department of Electrical Engineering before being tested and distributed to the main respondents. Testing the hypothesis using the correlation test and testing the significance of the hypothesis using the t-test was carried out to test the effect partially between the independent and dependent variables. The results showed that (1) there was a significant and positive effect on teacher pedagogic competence on learning outcomes (2) there was a significant and positive effect on teacher personality competence on learning outcomes (3) there was a significant and positive effect on teacher pedagogic competence and personality as a whole together on practical learning outcomes in the subject of electric power installation at SMK N 5 Padang. So, it can be concluded that pedagogic competence and teacher personality contribute to students' practical learning outcomes, so every teacher who teaches must develop each of these competencies so that student learning outcomes can improve properly.